Low recurrence rate of hepatocellular carcinoma following ledipasvir and sofosbuvir treatment in a real‐world chronic hepatitis C patients cohort. Issue 6 (8th March 2019) - Idilman, Ramazan; Demir, Mehmet; Aladag, Murat; Erol, Cihan; Cavus, Bilger; Iliaz, Raim; Koklu, Hayrettin; Cakaloglu, Yilmaz; Sahin, Memduh; Ersoz, Galip; Koksal, İftihar and Karasu, Zeki and Ozgenel, Meric and Turan, İlker and Gunduz, Feyza and Ataseven, Huseyin and Akdogan, Meral and Kiyici, Murat and Koksal, Aydın Seref and Akhan, Sila and Gunsar, Fulya and Tabak, Fehmi and Kaymakoglu, Sabahattin and Akarca, Ulus S and
Summary: The aims of the present study were to evaluate the efficacy and tolerability of ledipasvir/sofosbuvir (LDV/SOF) with or without ribavirin in the treatment of chronic hepatitis C (CHC) in patients with advanced liver disease and to analyse whether the use of LDV/SOF treatment is associated with a new occurrence of hepatocellular carcinoma (HCC) during and after LDV/SOF treatment. The Turkish Early Access Program provided LDV/SOF treatment to a total of 200 eligible CHC patients with advanced liver disease. The median follow‐up period was 22 months. All patients were Caucasian, 84% were infected with genotype 1b, and 24% had a liver transplantation before treatment. The sustained virological response (SVR12) was 86.0% with ITT analysis. SVR12 was similar among patients with Child‐Pugh classes A, B and C disease and transplant recipients. From baseline to SVR12, serum ALT level and MELD score were significantly improved ( P < 0.001). LDV/SOF treatment was generally well tolerated. Only one patient developed a new diagnosed HCC. Seventeen of the 35 patients, who had a history of previous HCC, developed HCC recurrence during the LDV/SOF treatment or by a median follow‐up of 6 months after treatment. HCC recurrence was less commonly observed in patients who received curative treatment for HCC compared with those patients who received noncurative treatment ( P = 0.007). In conclusion, LDV/SOF with or without ribavirin is an effective and tolerable treatment in CHC patients with advanced liver disease. Eradication is associated with improvements in liver function and a reduced risk of developing a new occurrence of HCC. Abstract : Ledipasvir and sofosbuvir with or without ribavirin is an effective and tolerable treatment in hepatitis C virus–infected patients with advanced liver disease. Eradication is associated with improvements in liver function and reduces the risk of developing a new occurrence of hepatocellular carcinoma.